Root canal retreatment using reciprocating and continuous rotary nickel-titanium instruments - de Souza, Patricia Fonseca; Oliveira Goncalves, Leonardo Cantanhede; Franco Marques, Andre Augusto; Sponchiado Junior, Emilio Carlos; Roberti Garcia, Lucas da Fonseca [UNESP]; de Carvalho, Fredson Marcio Acris (Thieme, 2015)
Objective: The complete filling material removal during endodontic retreatment is a clinical procedure difficult to achieve. The aim of this study was to evaluate the efficacy of reciprocating and continuous rotary nickel-titanium instruments used in root canal retreatment. Materials and Methods: Forty freshly extracted human premolars were cleaned and shaped bythe crown-down technique, followed by filling by the lateral compaction technique. The teeth were randomly separated into two groups (n = 20), according to the system used for filling material removal: G1 - Reciproc and G2 - ProTaper Universal Retreatment System. The teeth were photographed under operating microscope at ×8 magnification; and the total area of the root canal and remaining filling material were quantified. Results: No statistically significant difference (P > 0.05) in residual filling material was observed between groups; however, the time required for filling removal was significantly shorter for Reciproc system (P < 0.05). Conclusions: It was observed remaining filling material in all teeth, irrespective of the system used; however, root canal retreatment was faster when reciprocating motion was used.
Keywords: Reciprocating motion; Root canal retreatment; Rotary instruments